Procedural Justice, Therapeutic Jurisprudence, and Reoffending: Adjudicating Palestinian Minors in the West Bank’s Military Court - Farber, Shai (International journal of offender therapy and comparative criminology, 2023)
The Juvenile Military Court (JMC), established in 2009 in the West Bank, handles offenses perpetrated by Palestinian minors, consisting mostly of security-related violations. With the establishment of the JMC, and a subsequent three-stage legal reform in handling juvenile offenders, Palestinian minor suspects and defendants have been accorded various procedural rights. This study addresses the impact of these rights on the criminal careers of Palestinian minors appearing in the JMC. It first reviews the demographic profile of 8,301 minors handled by the JMC between 2000 and 2018, describes their offenses, and offense transition between their initial and second arrest. Using trend analysis, the study compares minors’ reoffending level in the years before and after the reform. The findings suggest significant differences in minors’ reoffending level between the years preceding and following the legal reform. Possible explanations for the findings are offered, and the article concludes with policy implications and directions for future research.